2019
DOI: 10.1002/hpm.2795
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the limitations of “quasi‐mandatory” approaches to enrolment in community‐based health insurance: Empirical evidence from Tanzania

Abstract: Summary In recent decades, a growing number of low‐income countries (LICs) have experimented with voluntary community‐based health insurance (CBHI), as an instrument to extend social health protection to the rural poor and the informal sector. While modest successes have been achieved, important challenges remain with regard to the recruitment and retention of members, and the regular collection of membership fees. In this context, there is a growing consensus among policymakers that there is a need to experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Another study in Dodoma, Tanzania, indicated that the implementation of the iCHF scheme improved after the involvement of community leaders. District authorities ensured that all local leaders were registered with the iCHF scheme and were informed as to its importance for the local community [23]. Therefore, in addition to an increased awareness of the health insurance scheme, other factors and barriers that influence enrollment need to be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in Dodoma, Tanzania, indicated that the implementation of the iCHF scheme improved after the involvement of community leaders. District authorities ensured that all local leaders were registered with the iCHF scheme and were informed as to its importance for the local community [23]. Therefore, in addition to an increased awareness of the health insurance scheme, other factors and barriers that influence enrollment need to be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another study from Tanzania found late stage of presentation, high proportions of aggressive histologic types of breast cancer, and a general lack of hormone and targeted receptor testing as contributory causes of high mortality in this region [ 8 10 ]. Additionally, therapies can be costly and 90% of women in Tanzania remain uninsured due to poor uptake of community-based health initiative schemes to increase insurance coverage for the low socioeconomic rural sector in Tanzania, which may contribute to inequality in access to healthcare [ 11 , 12 ]. Notably, data on precise medical regimens and the extent of treatment completion, as well as factors that influence treatment adherence, are lacking in this region, as in many LMICs.…”
Section: Introductionmentioning
confidence: 99%